EXPERIMENTAL EVALUATION OF THE OPERATIONAL CHARACTERISTICS OF INFORMATION PROTECTION SYSTEMS - A. M. Kadnova (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. The article is devoted to solving the practical problem of evaluating the operational indicator of the quality characteristics of the information security system usability. Methods. Evaluation of the operational characteristics of software systems can be performed theoretically and by measurement. Since the theoretical  assessment of operational characteristics has some disadvantages and  limitations, an experimental assessment is advisable. Simultaneously, it is  advisable to use the "Complexity" indicator of a typical operation performed by a security administrator, which expresses the average time of its  execution as the primary indicator of the quality of the functioning of the information security system usability. Measurement evaluation of the  operational characteristics of the information security system was carried out using the eye and mouse movement tracking methods. Results. The article provides an assessment of the "Complexity" indicator of all typical operations performed by the security administrator during the  Sentinel NT 3.0 ISS operation following the program documentation. Conclusion. The obtained values of the "Complexity" indicator can be used in the formation of a work plan for the operation and maintenance of  protected automated systems, in particular, with the installed information security system, when evaluating the timeliness of the performance of the  listed works, as well as when justifying the structure of the units responsible  for information protection and their quantity.